African acronyms and abbreviations : a handbook - Hall, David E. (David Eric) (Bloomsbury academic collections. Linguistics. Language studies., 2015)
"This is a directory of approximately 13,000 acronyms and abbreviations relating to Africa, including names of societies, institutions, associations, movements, government departments, agencies, ministries, committees, trade unions and commercial companies, from the 19th century onwards, which have been gathered from scholarly monographs and journal articles. The acronyms and abbreviations are international in scope, with many cross-references."--Bloomsbury Publishing